2011
DOI: 10.1155/2011/972168
|View full text |Cite
|
Sign up to set email alerts
|

A Therapeutic and Diagnostic Dilemma: Granular Cell Tumor of the Breast

Abstract: Six to eight percent of granular cell tumors are seen in the breast. Although mostly benign, they rarely have malignant features clinically and radiologically reminding of breast cancer. This may lead to a potential misdiagnosis of breast carcinoma and overtreatment of patients. The final diagnosis is made by immunohistochemical examination. We performed excisional biopsy on a patient who was diagnosed to have a breast mass. The histopathological examination of the mass revealed granular cell tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 9 publications
2
31
0
5
Order By: Relevance
“…Despite the success of screening, however, review of published cases suggests that until recently, most cases (70%) were found by palpation (Brown et al, 2011) as in our patient. Clinically GCT can resemble cancer due to firm consistency, nipple and/or skin retraction (Lack et al, 1980;Pergel et al, 2011). These features can be attributed to stromal desmoplasia that was observed in our case as well.…”
Section: Discussionsupporting
confidence: 73%
“…Despite the success of screening, however, review of published cases suggests that until recently, most cases (70%) were found by palpation (Brown et al, 2011) as in our patient. Clinically GCT can resemble cancer due to firm consistency, nipple and/or skin retraction (Lack et al, 1980;Pergel et al, 2011). These features can be attributed to stromal desmoplasia that was observed in our case as well.…”
Section: Discussionsupporting
confidence: 73%
“…GCTs account for an incidence of 0.5% among soft tissue tumors (3)(4)(5)(6). It may occur throughout the body, usually in the head and neck, skin or subcutaneous tissues of the trunk and upper extremities.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Costa Almeida et al (7) published a case report of GCT on the upper limb and reviewed 21 patients with this GCT localization from the literature. When occurring in the breast, as it occurs in 5-8% of all cases of GCT, they present mostly as painless rounded nodules (4,6). GCT of the breast may mimic breast cancer both clinically and radiologically (8-10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some GCTs of the breast have been documented to be coexisting with an ipsilateral infiltrating ductal carcinoma8–10 and also as a lesion occurring in mastectomy scars 11. The most frequent location is the upper-middle and medial quadrant, and the most frequent positive receptors are S-protein, periodic acid–Schiff (PAS) and diastase 9,10. It is more common in middle aged, premenopausal, black women and is extremely rare in male patients 3…”
Section: Introductionmentioning
confidence: 99%